Sex differences in immune protection in mice conferred by heterologous vaccines for pneumonic plague - Davies, Michael L.; Biryukov, Sergei S.; Rill, Nathaniel O.; Klimko, Christopher P.; Hunter, Melissa; Dankmeyer, Jennifer L.; Miller, Jeremy A.; Shoe, Jennifer L.; Mlynek, Kevin D.; Talyansky, Yuli; Toothman, Ronald G.; Qiu, Ju; et al. (Frontiers in Immunology, 2024)
Yersinia pestis is the etiological agent of plague, which can manifest as bubonic, septicemic, and/or pneumonic disease. Plague is a severe and rapidly progressing illness that can only be successfully treated with antibiotics initiated early after infection. There are no FDA-approved vaccines for plague, and candidates may be less effective against pneumonic plague than bubonic plague. Y. pestis is not known to impact males and females differently in mechanisms of pathogenesis or severity of infection. However, one previous study reported sex-biased vaccine effectiveness after intranasal Y. pestis challenge. As part of developing a safe and effective vaccine, it is essential that potential sex differences are characterized. In this study we evaluated novel vaccines in male and female BALB/c mice using a heterologous prime-boost approach and monitored survival, bacterial load in organs, and immunological correlates. Our vaccine strategy consisted of two subcutaneous immunizations, followed by challenge with aerosolized virulent nonencapsulated Y. pestis. Mice were immunized with a combination of live Y. pestis pgm-pPst-Δcaf1, live Y. pestis pgm-pPst-Δcaf1ΔyopD, or recombinant F1-V (rF1-V) combined with adjuvants. The most effective vaccine regimen was initial priming with rF1-V, followed by boost with either live attenuated strain. However, this and other strategies were more protective in female mice. Males had higher bacterial burden and differing patterns of cytokine expression and serum antibody titers. Males also had impaired synergy between vaccination and antibiotic treatment. This study provides new knowledge about sex differences in plague-vaccine efficacy and the immunological factors that differ between male and female mice.